Effects of fertilization on soil nematode communities in an alpine meadow of Qinghai-Tibet plateau - Qi, Yanwen; Sun, Xinhang; Peng, Sichen; Tan, Xiaodan; Zhou, Shurong (Frontiers in Ecology and Evolution, 2023)
Nitrogen and phosphorus are important nutrient elements for plants and underground organisms. The nematode is an important part of the soil food web. Although many studies have explored the effects of fertilization on soil nematode community structure, little is known about the response mechanism of the nematode community to fertilization. In this study, we investigated the diversity and functional diversity of soil nematode communities, as well as soil physicochemical properties, root functional traits, and plant richness. We explored the response mechanism of soil nematode communities to nitrogen and phosphorus fertilizer. Nitrogen fertilizer increased the abundance and richness of bacterivorous nematodes, while phosphorus fertilizer decreased the total abundance of bacterivorous nematodes. Meanwhile, the diversity of the nematode community was significantly affected by soil physicochemical properties and plant root functional traits. Therefore, our study revealed the effects of nitrogen and phosphorus fertilizer on soil nematode community diversity and functional diversity. Exploring the response mechanism of soil nematode communities to fertilization interference provides further evidence for the role of nematodes in maintaining the function of subsurface ecosystems.